The Influence Of Character, Competence And Literacy Digital To Employee Performance At Smkn 1 Bengkulu Selatan - Ogriansyah, Gioni; Anggriani , Ida; Effendi , Bahman (Jurnal Pusat Manajemen, 2025)
The purpose of this study is to determine  the influence of Character, Competence, and Digital Literacy on Employee Performance at SMK Negeri 1 South Bengkulu. The type of research used in this study is a quantitative method. Based on the results of multiple linear regression analysis, the equation was obtained: Y = 3.431 + 0.268X₁ + 0.147X₂ + 0.506X₃ +0,752. The results of the partial test (t-test) showed that  the Character variable (X₁) had a positive and significant effect  on Employee Performance (Y) with a tcal value = 7.636 > ttable = 1.983 and significance = 0.000 < 0.05. Competency Variable (X₂) also has  a positive and significant effect  on Employee Performance with tcount = 3.983 > ttable = 1.983 and significance = 0.000 < 0.05. Furthermore,  the Digital Literacy variable (X₃) provided the most dominant influence, with tcount = 17.953 > ttable = 1.983 and significance = 0.000 < 0.05. Simultaneously (F test), the three variables had a significant effect on Employee Performance, with the value of Fcal = 1049.012 > Ftable = 3.07 and significance = 0.000 < 0.05. The determination coefficient value (R²) of 0.969 shows that Character, Competence, and Digital Literacy together  are able to explain 96.9% of the variation in Employee Performance, while  the remaining 3.1% is explained by other factors outside this research model. Thus, it can be concluded that the better the character, the higher the competence, and the stronger the digital literacy of employees, the higher the performance of employees at SMK Negeri 1 South Bengkulu.